Heidegger in naraščajoča sodobna družbeno-ekološka kriza - Kirn, Andrej (Teorija in praksa, 2011)
Rather than aiming to give the most proper interpretation of Heidegger, the author's objective is to discover the ecological dimensions of his thinking. This dimension lies particularly in the broad frame of his understanding of humanism and of technology. Heidegger's understanding of metaphysics, technology, and humanism can be linked with the eco-social sustainability paradigm, the idea of the limits to growth and the abandonment of the paradigm of permanent economic growth. Heidegger does not link the understanding of being with the social being. Similarly, he does not link the origin and the development of modern natural sciences and technology with the capitalist society, but with the development of the productionistic metaphysics. A 'relaxed' attitude towards technology will not alter its ecological consequences. In the existing intellectual and practical circumstances, a thorough analysis of the relation between Heidegger and Marx would be more productive than the analysis of the relation between Heidegger and Nazism.
Keywords: Heidegger, Martin, 1889-1976; Philosophy; Humanism; Filozofija; Humanizem; Social crisis; Družbena kriza; Ecological crisis; Ekološka kriza; družbene spremembe; zgodovinskost